AIR, SANITASI, DAN STUNTING DI INDONESIA : NARRATIVE REVIEW - Puji Analia; Mateus Sakundarno Adi; Achmad Zulfa Juniarto (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Stunting is a condition of growth failure in toddlers (under 5 years) due to chronic nutritional problems that cause children to be short for their age. Globally, WHO (2022) estimates that as many as 148.1 million (22.3%) toddlers experience stunting, most of whom are in Asian (52%) and African (43%) countries, one of which is Indonesia. Poor water and sanitation conditions are often found in areas with a high prevalence of stunting. So far, a lot of research has been conducted on stunting in Indonesia, but it only focuses on nutrition/ food. Water and sanitation factors have not been researched much or have not receive much attention, even though their influence is quite large.Objectives: This study aims to analyze the association between water and sanitation factors and the incidence of stunting in Indonesia.Methods: The method used in writing this article is a narrative review. A search for several electronic databases was conducted between January - March 2025 using Scopus, Science Direct, and PubMed published between 2020-2025. The search keywords used included “Water “AND” Sanitation “AND” Stunting.Results: A review of 22 articles found that water factors (source of clean water, quality of clean water, source of drinking water, access to drinking water, drinking water treatment) and sanitation (use of toilets, healthy toilets, ownership of toilets, open defecation behavior and improper disposal of toddler feces) were all associated with stunting in children under five years of age.Conclusion: Inadequate water and sanitation factors are associated with stunting in toddlers in IndonesiaKeywords : Water; Sanitation;Toddlers; Stunting; Indonesia ABSTRAKLatar belakang: Stunting mencerminkan kondisi gagal tumbuh pada anak balita (bawah 5 tahun) akibat masalah gizi kronis yang menyebabkan anak menjadi pendek untuk usianya. Secara global, WHO (2022) memperkirakan sebanyak 148.1 juta (22.3%) anak balita mengalami stunting, sebagian besar berada di negara-negara Asia (52%) dan Afrika (43%), salah satunya Indonesia. Kondisi air dan sanitasi yang buruk, sering ditemukan di daerah dengan prevalensi stunting yang tinggi. Selama ini penelitian terkait stunting di Indonesia sudah banyak dilakukan namun hanya berfokus pada gizi/ makanan, faktor air dan sanitasi masih belum banyak di teliti atau tidak terlalu diperhatikan padahal pengaruhnya cukup besarTujuan: Penelitian ini bertujuan untuk menganalisis hubungan faktor air dan sanitasi dengan kejadian stunting di Indonesia.Metode: Metode yang digunakan dalam penulisan artikel ini adalah narrative review. Pencarian beberapa electronic database dilakukan pada bulan Januari – Maret 2025 melalui Scopus, Science Direct, dan PubMed yang terbit pada 2020-2025. Keywords pencarian yang digunakan meliputi “Water “AND” Sanitation “AND” Stunting. Hasil: Tinjauan terhadap 22 artikel menemukan bahwa faktor air (sumber air bersih, kualitas air bersih, sumber air minum, akses terhadap air minum, pengolahan air minum) dan sanitasi (penggunaan jamban, jamban sehat, kepemilikan jamban, perilaku buang air besar sembarangan dan pembuangan kotoran balita tidak tepat) berhubungan dengan stunting pada anak di bawah usia lima tahun.Simpulan: Faktor air dan sanitasi yang tidak memadai berhubungan dengan kejadian stunting pada anak balita di Indonesia Kata Kunci : Air; Sanitasi; Balita; Stunting; Indonesia